Effects of marketing strategy on performance: a study of Indonesian organizations - Ishak, Asmai (Curtin University, 2002)
This research provides empirical evidence on the implementation of the strategic marketing planning in the context of Indonesia, a newly industrialized country. Drawing from a contingency theory, the research posits that the credibility of marketing strategy depends on the external business environments and its formulation process. The credibility of marketing strategy and the strategy formulation process, in turn, determine the effectiveness of the implementation of the strategy in achieving the desired performance. The causal relationships amongst these variables were then analyzed by structural equation model using LISREL 8.30 program. The primary data for this study were collected through structured interviews with the Marketing Managers of 219 Indonesian companies. The results of the study not only strengthen the notion of the influence of external business environments on the actions of organizations, such as the credibility of marketing strategy, but also confirm the belief of the importance of an innovative culture in implementing strategic marketing planning. The study also identifies that marketing managers play a pivotal role in the formulation and implementation of the strategy. Within the scope of the strategy formulation, marketing managers as boundary spanners of their companies provide the decision makers with current and up to date strategic issues, which in turn enhance the credibility of the formulated strategy. On the other hand, within the strategy implementation, the managers with their autonomy conduct evaluation and control of the marketing strategy, and adjust the strategy to any significant environmental changes to achieve the desired performance.These findings not only support the view that it is inappropriate to separate the strategy formulation from its implementation aspects, but also corroborate the importance of the fit between marketing strategy and its external and internal environments to gain the desired performance. Finally, the use of Indonesian companies as the sample of this study and the consistencies of most of the results of the study with the existing findings reveal that the results are applicable in both industrialized and newly industrialized countries.